Workforce Sustainability in U.S. Construction: Impact of Health and Wellbeing, Diversity, Equity, Community, and Connectivity on Job Satisfaction and Retention - Bonilla, Minerva; Gbiengu, Prosper; Nnaji, Chukwuma (Revista Ingeniería de Construcción, 2024)
The construction industry is currently experiencing high turnover rates and a shortage of skilled labor, which presents significant challenges to workforce sustainability. This study examines the relationship between key workforce sustainability attributes—diversity, health and wellbeing (H&W), equity, community, and connectivity—and their impact on job satisfaction and attrition intentions among Latino/Hispanics, Black or African Americans, and Caucasian workers within the U.S. construction sector. Utilizing data from 95 fieldworkers, correlation analysis indicates that diversity, equity, and community play crucial roles in influencing job satisfaction and retention. These insights provide strategic guidance for promoting a sustainable workforce through inclusive and supportive workplace practices.